2021
DOI: 10.7554/elife.62552
|View full text |Cite
|
Sign up to set email alerts
|

ß-arrestin 2 germline knockout does not attenuate opioid respiratory depression

Abstract: Opioids are perhaps the most effective analgesics in medicine. However, between 1999 to 2018, over 400,000 people in the United States died from opioid overdose. Excessive opioids make breathing lethally slow and shallow, a side-effect called opioid induced respiratory depression. This doubled-edged sword has sparked the desire to develop novel therapeutics that provide opioid-like analgesia without depressing breathing. One such approach has been the design of so-called 'biased agonists' that signal through s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…However, a recent study demonstrated that an opioid receptor ligand that does not induce μOR βarrestin 2 dependent signaling still temporarily induces opioid induced respiratory depression. [24] Moreover, some results, [25] refute the foundational model that β-arrestin 2 selectively mediates opioid induced respiratory depression and suggest that reinvestigate the mechanism of biased agonism in vivo in the future. Nevertheless, there are also many recent reports showed that G-protein-biased μOR agonists worked, [26][27][28] and there are conversely results which need to be further concerned.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a recent study demonstrated that an opioid receptor ligand that does not induce μOR βarrestin 2 dependent signaling still temporarily induces opioid induced respiratory depression. [24] Moreover, some results, [25] refute the foundational model that β-arrestin 2 selectively mediates opioid induced respiratory depression and suggest that reinvestigate the mechanism of biased agonism in vivo in the future. Nevertheless, there are also many recent reports showed that G-protein-biased μOR agonists worked, [26][27][28] and there are conversely results which need to be further concerned.…”
Section: Introductionmentioning
confidence: 98%
“…As described above, core premise for the development of μOR biased agonists is that β‐arrestin2 dependent signaling provides a molecular mechanism to dissociate analgesia from respiratory depression. However, a recent study demonstrated that an opioid receptor ligand that does not induce μOR β‐arrestin 2 dependent signaling still temporarily induces opioid induced respiratory depression [24] . Moreover, some results, [25] refute the foundational model that β‐arrestin 2 selectively mediates opioid induced respiratory depression and suggest that reinvestigate the mechanism of biased agonism in vivo in the future.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the G protein-dependent signaling pathway mediates pharmacological effects, such as analgesia and sedation, whereas the ß-arrestin-dependent signaling pathway mediates respiratory depression (Kelly, 2013). At present, the original suggestion that ß-arrestin2 signaling plays a key role in opioid-induced respiratory depression has been questioned (Kliewer et al, 2020;Bachmutsky et al, 2021). Even so, there is still a growing interest in the development of functionally selective G protein-coupled receptor (GPCR) ligands facilitated by hopes of producing more effective drugs with reduced side effects (Wacker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These observations strongly suggest an important unresolved gap between the concept of biased agonism and functional selectivity. Furthermore, most recent studies reported that mutant mice lacking β-arrestin 2 or expressing phosphorylation-deficient MOP, which does not recruit β-arrestin 2, also presented with side effects following opioid administration [11][12][13] . These results critically raise the question as to whether recruitment of β-arrestin 2 to MOP is the true culprit that triggers opioid side effects 14 .…”
Section: Introductionmentioning
confidence: 99%